Algae-Derived Polysaccharides Promote Growth Performance by Improving Antioxidant Capacity and Intestinal Barrier Function in Broiler Chickens - Liu, Wen-Chao; Guo, Yan; Zhao, Zhi-Hui; Jha, Rajesh; Balasubramanian, Balamuralikrishnan (Frontiers in Veterinary Science, 2020)
This study aimed to determine the efficacy of dietary algae-derived polysaccharides (ADPs) from Enteromorpha on growth performance, intestinal morphology, intestinal permeability, and antioxidant capacity in serum, liver, and intestinal mucosa of broilers. Three hundred and ninety six day-old male chicks were randomly assigned to six dietary treatments containing 0 (Control), 1,000, 2,500, 4,000, 5,500, and 7,000 mg ADP/kg basal diet in a 35 day feeding trial. During day 1–21, compared with the control group, dietary 1,000–7,000 mg/kg ADP supplementation improved the average daily gain (ADG) and feed conversion ratio (p < 0.05). Overall (day 1–35), dietary inclusion of 1,000 mg/kg ADP increased the final body weight and ADG (p < 0.05). Besides, on day 21, dietary 2,500 mg/kg ADP supplementation increased the serum catalase (CAT) and liver total superoxide dismutase (T-SOD) activities (p < 0.05), whereas dietary 1,000–5,500 mg/kg ADP supplementation decreased malondialdehyde (MDA) contents in serum and liver (p < 0.05). On day 35, supplementation of 1,000 mg/kg ADP increased the serum glutathione peroxidase and CAT activities and liver T-SOD activities (p < 0.05). It decreased the MDA level of serum and liver (p < 0.05). Also, dietary 2,500 mg/kg ADP increased the villus height of jejunum and ileum on day 21 (p < 0.05), and dietary 4,000 mg/kg ADP increased the villus height of duodenum and ileum on day 35 (p < 0.05). On day 21, dietary 4,000 mg/kg ADP increased the CAT activities of the duodenum and T-SOD activities of jejunum and ileum and decreased the MDA contents in the duodenum, jejunum, and ileum (p < 0.05). On day 35, dietary inclusion of 1,000–7,000 mg/kg ADP reduced MDA contents of duodenum and jejunum (p < 0.05). Furthermore, dietary inclusion of ADP at 1,000–7,000 mg/kg decreased serum DAO activities at day 21 and day 35 (p < 0.05), and the serum D-lactic acid concentration was reduced by dietary supplementation of 1,000, 2,500, and 7,000 mg/kg ADP on day 21. In conclusion, dietary ADP exerted beneficial effects on growth performance, antioxidant capacity, and gut health in broilers; based on the studied parameters, the appropriate recommended dose is 1,000–4,000 mg/kg. These findings provided new insights into the potential application of ADP as natural growth promoters in broilers.